Left distal sciatic giant solitary myxoid neurofibroma: a case report & literature review - Thawabtah, Fatima az-Zahra’; Idkedek, Mayar; Nimer, Hafez (Frontiers in Surgery, 2024)
Introduction: Neurofibroma, a rare benign tumor of the peripheral nervous system, can manifest anywhere along a nerve from the dorsal ganglion to its terminal branches. Myxoid neurofibroma can present as a solitary non-tender nodule and is often confirmed by positive immunohistochemical staining for S-100 protein. However, in 50% of cases, neurofibromas are associated with neurofibromatosis. Case Presentation: We present a case of a 34-year-old male with mild pain in the posterior part of his left thigh, accompanied by a slowly-growing swelling particularly noticeable when flexing his knee. It had gradually increased in size over several months, which the patient observed as a decrease in the degree of knee extension. Initial biopsy indicated schwannoma with no evidence of malignancy. Four years later, the swelling increased in size and necessitated resection surgery, revealing an irregular giant tumor measuring 8 *6 *4.5 cm, adherent to adjacent structures, including the femur, muscles, popliteal artery and vein, and a branch of the sciatic nerve. Pathological analysis reclassified the diagnosis to low-grade myxoid neurofibroma. Follow-up MRI three months later showed gross total resection without residual or recurrence of the tumor. Discussion: Solitary neurofibromas are often small in size, ranging from 1 to 2 cm in the greatest dimension. Alternatively, tumors that occur as a part of genetic neurofibromatosis tend to be multiple and often grow to large sizes. In our case, the patient didn't have neurofibromatosis as he didn't meet its diagnostic criteria despite having a giant tumor measuring approximately 8*6*4.5 cm. To our knowledge, this is the first report of giant myxoid solitary neurofibroma of the thigh apart from neurofibromatosis. Thus, this type of tumor should be considered in the differential diagnosis of tumors at this location.